DYNAMICS OF ARABIC LANGUAGE LEARNING IN THE GEN Z ERA: CHALLENGES AND OPPORTUNITIES - Rocyhan Yasin (PT. Jurnal Center Indonesia Publisher, 2025)
Arabic in the Generation Z era faces significant learning changes along with the development of digital technology and the unique characteristics of this generation known as digital natives . This study aims to identify challenges and opportunities in the Arabic language learning process among Gen Z using a literature review approach to various recent studies. The research method uses a literature review by reviewing 30 articles in several published national journals. The results of the study indicate that the main challenges include low digital literacy among educators, limited technological infrastructure, and the dominance of traditional learning methods that are less attractive to Gen Z. However, on the other hand, there are great opportunities through the use of technology such as social media, interactive learning applications, gamification, and blended learning approaches that can increase motivation and learning participation. This study recommends the need for curriculum development that is adaptive to the needs of Gen Z, digital competency training for teachers, and the integration of digital media that is relevant to the learning styles of the younger generation. By utilizing existing opportunities, Arabic language learning can be more contextual, interesting, and effective for today's generation